Development of Braille Codes for Qur’anic Literacy among Muslims with Blindness in Nigeria - Rasheed Adekunle ABILU ABILU; Jamal Abioye Adio; Akinbode P. OLAOYE; Wasiu Ademola JIMOH; Aminullahi Adetoro YUSUFF; Ibrahim A. YEQEEN YEQEEN; Abeeb A ADEWUYI ADEWUYI; Fatimoh Adeola ADEWOYIN ADEWOYIN (Sinergi International Journal of Islamic Studies, 2025)
Access to the Qur’an in Braille formats for Muslims with blindness in Nigeria is limited due to the scarcity, high production cost, lack of basal reader, and uneven distribution of Braille copies. These constraints restrict opportunities for independent reading practice and affect the development of accurate tajweed application and sustained Qur’anic literacy among Muslims with blindness in Nigeria. This study developed Arabic Braille codes to enhance Qur’anic reading fluency among Muslims with blindness in Nigeria using a Design-Based Research (DBR) approach, which involves iterative development, expert validation, and field testing. The standard Arabic Braille alphabet was retained, while additional codes were developed for key recitation features, including elongation markers (al-madd), nasalization signs, and pause/stop signs. The codes were evaluated using a 24-item usability and accuracy instrument administered to 32 participants with blindness drawn from three specialized educational centers in Nigeria during a six-week guided reading intervention. Internal consistency reliability of the instrument yielded Cronbach’s α = 0.82. Inter-rater agreement on the accuracy of participants’ transcriptions of selected symbols, assessed independently by five experts in Qur’anic studies and special education, produced κ = 0.85. Qualitative feedback from participants and instructors indicated improved readability, learnability, and cultural acceptability of the codes. The findings suggest that the developed Braille code are viable for supporting Qur’anic literacy among Muslims with blindness. The study therefore recommends national adoption of the developed codes, large-scale production of Braille Qur’an using these standards, and the organization of Qur’anic Braille training workshops.